Restoration of Coastal Beach Forming Ecosystem Processes through Shoreline Armoring Removal of a Former Mine Site Increases Our Understanding of Coastal Resiliency and Large Scale Landslides Along the Northeast Pacific Coastline. Issue 5 (28th May 2021) - Shaffer, Anne; Parks, Dave; Michel, Jamie; Simonsen, Kirsten; Campbell, Katrina; Oxborrow, Bob; Hall, Jonathan; Weslowski, Jennifer
ABSTRACT: Coastal zones are important components of marine ecosystems that link upland and marine areas, and are often maintained by landslides, though these habitat forming processes are poorly understood. They are also often sites of commercial development, including mining, and restoration.  In this ecosystem restoration project, we rapidly removed a large volume of shoreline armoring from the perimeter of an intertidal earthen filled mine structure. The remaining feature mimicked the toe of a large land slide characteristic of the region.  Physical and ecological monitoring allowed us to understand how coastal ecosystems respond to large scale coastal sediment processes, including landslide function that forms them, and restoration actions to restore them. As a course of restoration, over 22, 936 m 3  of non-native armor totaling 0.47 hectares was rapidly removed from the perimeter of a 2.8 hectare earthen pier. Three years after removal, the feature is less than half its original configuration (area). Beach composition and ecological community of the restoration area responded positively relative to pre-project conditions and to the control site. Applying these results to historic deep seated landslides that define coastal zones of the region, we conclude that nearshore ecosystems are resilient and respond similarly to episodic natural and restored large-scale hydrodynamic processes.